2000
DOI: 10.1016/s0092-8674(00)80847-8
|View full text |Cite
|
Sign up to set email alerts
|

PKA Phosphorylation Dissociates FKBP12.6 from the Calcium Release Channel (Ryanodine Receptor)

Abstract: The ryanodine receptor (RyR)/calcium release channel on the sarcoplasmic reticulum (SR) is the major source of calcium (Ca2+) required for cardiac muscle excitation-contraction (EC) coupling. The channel is a tetramer comprised of four type 2 RyR polypeptides (RyR2) and four FK506 binding proteins (FKBP12.6). We show that protein kinase A (PKA) phosphorylation of RyR2 dissociates FKBP12.6 and regulates the channel open probability (Po). Using cosedimentation and coimmunoprecipitation we have defined a macromol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

98
2,146
19
42

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,874 publications
(2,305 citation statements)
references
References 33 publications
98
2,146
19
42
Order By: Relevance
“…A major deficit in failing myocytes is the reduced Ca 2+ content of the SR, which is related to decreased expression and activity of the SR Ca 2+ -ATPase [84,92,146,153] and an increased Ca 2+ leak of the RyR2 due to hyperphosphorylation [84,94,112,122]. These defects, potentially aggravated by L-type Ca 2+ channel dysfunction [41,71,81,86,113,131,146,184] or t-tubular derangement [32,86,115,145,184], lead to a smaller and more dyssynchronous SR Ca 2+ release during an AP, resulting in slower rates of increase and decay of [Ca 2+ ] c , but higher diastolic [Ca 2+ ] c compared to normal cardiac myocytes [17,81,113,115,146,184].…”
Section: Pathophysiological Aspects Defects In Ec Coupling In Chronicmentioning
confidence: 99%
“…A major deficit in failing myocytes is the reduced Ca 2+ content of the SR, which is related to decreased expression and activity of the SR Ca 2+ -ATPase [84,92,146,153] and an increased Ca 2+ leak of the RyR2 due to hyperphosphorylation [84,94,112,122]. These defects, potentially aggravated by L-type Ca 2+ channel dysfunction [41,71,81,86,113,131,146,184] or t-tubular derangement [32,86,115,145,184], lead to a smaller and more dyssynchronous SR Ca 2+ release during an AP, resulting in slower rates of increase and decay of [Ca 2+ ] c , but higher diastolic [Ca 2+ ] c compared to normal cardiac myocytes [17,81,113,115,146,184].…”
Section: Pathophysiological Aspects Defects In Ec Coupling In Chronicmentioning
confidence: 99%
“…Even though circulating levels of catecholamines are constitutively higher than in healthy persons, beta-adrenergic receptors appear to be down-regulated, and the robust responsiveness to agents such as isoproterenol seen in healthy heart cells is severely attenuated (Marks, 2001;Chien et al, 2003). Biochemical studies have indicated that this abnormal, sustained "hyperadrenergic" state leads to excess phosphorylation of RyRs (Marx et al, 2000), although this result remains controversial (Jiang et al, 2002). Complementary planar lipid bilayer studies of RyR gating have predicted that this hyperphosphorylation will lead to increased RyR open probability.…”
Section: The Paradoxmentioning
confidence: 99%
“…Complementary planar lipid bilayer studies of RyR gating have predicted that this hyperphosphorylation will lead to increased RyR open probability. Additional key results are that RyR phosphorylation causes dissociation of FKBP12.6 from the RyR macromolecular complex (Marx et al, 2000) and that in HF RyRs display decreased binding to this regulatory protein (Ono et al, 2000). Together, one might expect that these effects would lead to increased Ca 2+ leak from the SR and an increased rate of Ca 2+ sparks in quiescent ventricular myocytes isolated from failing hearts.…”
Section: The Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms behind this reduction of diastolic cardiac muscle fluctuation were not revealed by the present study. Considering the important role of RyR function in SL fluctuation, the effect of Celacade on SL fluctuation in MI trabeculas might involve a regulatory step of the RyR functional pathway, possibly including RyR phosphorylation by either protein kinase A or Ca 2+ -calmodulin-dependent protein kinase II (2,(15)(16)(17), or alteration of stoichiometry of the FK506 binding protein 12.6 to the channel (18), and increased oxidative stress in the MI heart (19).…”
Section: Effects Of Celacade On Sl Fluctuationsmentioning
confidence: 99%